A STUDY ON EFFECTIVENESS OF GAMIFIED LEARNING AMONG ARTS & SCIENCE COLLEGE STUDENTS WITH SPECIAL REFERENCE TO CHENNAI CITY - et al., NIVEDDA MK (International Journal of Advanced Science and Technology, 2019)
PURPOSE: The purpose of this study is to find out the effectiveness of gamified learning among arts and science college students in Chennai city. The other purpose of this study is to analyze the factors that influence towards gamified learning.